Comparative analysis of feeding strategies and post mortem aging time on the oxidative status and color of the longissimus thoracis et lumborum muscle in Braford steers - María Sofía Castaño Ledesma; Gustavo Adolfo Palma; Gustavo Adolfo Palma; Claudio Darío Borsarelli; Claudio Darío Borsarelli; María Sumampa Coria; María Sumampa Coria (Frontiers in Animal Science)
The impact of corn silage supplementation and post mortem aging on the antioxidant status in longissimus thoracis et lumborum (LTL) muscle was assessed using micro-spectroscopic techniques. A total of 30 Braford steers were utilized in the study. Of these, 15 animals were supplemented with corn silage for 120 days, while the remaining animals were fed exclusively on pasture. LTL steak samples were aged for 2, 7, 14, and 21 days at a temperature of 2 ± 1°C, under conditions of darkness and vacuum. Several colorimetric assays were employed to evaluate the antioxidant capacity of both enzymatic and non-enzymatic origin, as well as the levels of protein and lipid oxidation. The content of heme pigment was determined by a spectrophotometric assay, while the fluorescence fingerprint of beef was evaluated by fluorescence spectroscopy excitation-emission matrices (FEEM). Additionally, the muscle microstructure was analyzed via scanning electron microscopy (SEM). The results demonstrated that the finishing system did not exert any discernible influence on the rates of lipid oxidation, antioxidant capacity, or muscle microstructure. However, the carbonyl content and total myoglobin exhibited higher levels in the corn silage-supplemented animals. Conversely, during aging period, data revealed that lipid degradation proceeded at a faster rate than protein oxidation, accompanied by a notable enhancement in antioxidant capacity within the hydrophilic meat extracts. In contrast, the lipophilic extracts demonstrated a reduction in both enzymatic and non-enzymatic antioxidant capabilities with the progression of post mortem aging. The aforementioned alterations were accompanied by a reduction in the muscle microstructure during the aging process. The results demonstrate that finishing steers with or without corn silage over 120 days results in comparable and satisfactory beef quality after 21 days of vacuum aging. It can be concluded that 21 days of storage compensates the antioxidant status obtained by feeding strategies in fresh meat. Furthermore, SEM and FEEM techniques allowed for a precise evaluation of the microstructure and oxidative status, suggesting that these methods could be employed in future assays.